The challenge of fundamentalism : political Islam and the new world disorder - Tibi, Bassam (Comparative studies in religion and society., 2002)
A text which suggests that Islamic fundamentalism is a result of Islam's confrontation with modernity. The author provides an analysis of the politicization of religion and, as an alternative to fundamentalism, he proposes a compact based on secular democr.